2022
DOI: 10.1002/aenm.202201843
|View full text |Cite
|
Sign up to set email alerts
|

Real‐Time Mimicking the Electronic Structure of N‐Coordinated Ni Single Atoms: NiS‐Enabled Electrochemical Reduction of CO2 to CO

Abstract: as a side reaction, thereby diminishing the selectivity of the CO 2 RR. To increase the selectivity and catalytic activity of the CO 2 RR, several materials, such as Ag, Cu, Au, Sn, N-coordinated Ni single atoms (NiNC), FeNC, and so on have been reported as electrochemical catalysts. [4][5][6][7][8][9][10][11][12] These catalysts possess high H* chemisorption energies and moderate *COOH chemisorption energies, suppressing the HER and accelerating formation of carbonaceous products. In contrast, other materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Recent studies on CO 2 R with Cu 2 Se have shown that the presence of Se 2– with Cu­(I) resulted in ligand (Se)-to-metal (Cu) back-bonding, which increases the electron density on Cu to have better CO adsorption . In the NiS or CuS nanoparticle studied as the cathode for CO 2 R, the metal center acted as the active species for reduction, while they initially reduced to Ni 0 /Cu 0 . A partial loss of sulfide from the NiS structure may also be associated with the reduction …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on CO 2 R with Cu 2 Se have shown that the presence of Se 2– with Cu­(I) resulted in ligand (Se)-to-metal (Cu) back-bonding, which increases the electron density on Cu to have better CO adsorption . In the NiS or CuS nanoparticle studied as the cathode for CO 2 R, the metal center acted as the active species for reduction, while they initially reduced to Ni 0 /Cu 0 . A partial loss of sulfide from the NiS structure may also be associated with the reduction …”
Section: Resultsmentioning
confidence: 99%
“…In the NiS or CuS nanoparticle studied as the cathode for CO 2 R, the metal center acted as the active species for reduction, while they initially reduced to Ni 0 /Cu 0 . A partial loss of sulfide from the NiS structure may also be associated with the reduction …”
Section: Resultsmentioning
confidence: 99%
“…X-ray absorption spectroscopy is currently the most widely applied operando spectroscopy to study the evolution of catalyst structure during CO 2 RR under high current density conditions. 18,113,115,118–123 Because of its great compatibility with flow cell designs, the operando measurement requires only minor cell modifications (Fig. 5).…”
Section: Operando Characterization Of Co2 Electrolyzersmentioning
confidence: 99%
“…12 Ni–N–C materials were found to be excellent catalysts for CO production, but their long-term stability is a major issue, particularly at high current densities. 18,68,121 This might be overcome by understanding the evolution of the active metal sites during operation. A catalyst containing dinuclear Ni 2 sites anchored on a N–C matrix exhibited 94.3% FE towards CO at 150 mA cm −2 current density in a microfluidic flow cell.…”
Section: Operando Characterization Of Co2 Electrolyzersmentioning
confidence: 99%
See 1 more Smart Citation